CURCHASES IN THE FIELD OF MILITARY EDUCATION, PROBLEMS AND SOLUTIONS TO TEACH LANGUAGE TEACHING - Xatamova Gulbaxor Abdumo'min qizi; Yembergenova Aysuluv Aydosbayevna (Sciental Journals Publishing, 2025)
This article will analyze the main problems in the field of military education in teaching language teaching. Curss will consider problems with language learning difficulties, motivation, content and methodology of lessons. It is also proposed to address these issues, innovative pedagogical approaches, interactive methods and communicative teaching methods. The article provides practical recommendations for improving language knowledge in military educational process and training effective.
Keywords: Military education, cadets, language teaching, challenges, communications, pedagogical methods, motivation